Krisztina Egerszegi's Full Stroke at 25 m of Her 100 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992 - Rushall, B. S. (1999)
Video pictures (14 frames) and the appropriate technical/ biomechanical explanations for Krisztina Egerszegi's Full Stroke at 25 m of Her 100 m Backstroke Gold Medal Swim at the Barcelona Olympic Games 1992.